Social Dynamic Status and its Reflection on Use of Family Planning Methods in an Indian Village: The Case of 'Gaura' Village (UP), India - Singh, Vimalesh Kumar; Singh, M. B. (The Third Pole: Journal of Geography Education, 2009)
Present paper aims at examining the recent transformation of the village society, which is caste ridden, conservative and sluggish to adopt new innovations. The paper is mainly based on primary data collected through interview schedules from 80 families and 123 married women respondents on stratified random basis from Gaura village of Mirzapur District, Uttar Pradesh. On the basis of social dynamic status in a rural population of Gaura village the study pinpoints that Yadav, Gupta, Lohar, and Harijan (Scheduled caste) castes are static communities while Kurmi has been found single progressive caste. Brahmin and Kumhar are categorized as retrogressive castes. The paper also highlights the position of spouse on the practice of family planning methods. This study was undertaken to assess the extent of awareness among married women towards the various aspects of family planning. It was found that majority of the respondents had knowledge and awareness about various aspects of family planning but its adoption is of low magnitude. Women were the major users of permanently contraceptives (tubectomy) as contrary to men. Some women were found with the use of oral pills but the use of loops, condom and copper-T was almost absent in the study village. DOI: http://dx.doi.org/10.3126/ttp.v5i0.1953 The Third Pole, Vol. 5-7, PP 52-61:2007